Navigating crisis with empathy and innovation: Women’s transformational leadership in improving the welfare of local communities - Esa Septian; Septi Wulandari; Obi Pratama (JURNAL ILMU SOSIAL, 2025)
This study aims to analyze the transformational leadership style adopted by women leaders in Village-Owned Enterprises (BUM Desa) in transferring positive values, building trust, and innovation during the COVID-19 pandemic. The type of research used is descriptive qualitative research with a case study approach. The methods of data collection used in this study are observation, interviews, documentation, and data triangulation. The findings of this study indicate that: 1) The transformational leadership style in the existence of BUM Desa Binangun Jati Unggul has a strong influence in instilling positive values, being able to inspire subordinates, and being the key to innovative problem-solving. 2) Women have been effective in increasing the productivity of business units and showing the persistence of spirit in the joint movement in facing the COVID-19 pandemic crisis. However, problems are still related to the need for more skill development and the lack of employee independence at work. Women's transformational leadership style has presented a new concept of solid gender characteristics as an asset for a leader in making inclusive and change-oriented decisions. The women's leadership paradigm has underpinned that women can become ideal leaders to be relied upon in building gender equality. This is to achieve the vision and mission goals of Binangun Jati Unggul Village-Owned Enterprise in improving the welfare of the local community.